Ovoz rejissorining ish jarayonidagi kognitiv va texnik kamchiliklar: Psixoakustik tahlil va ularni bartaraf etishning zamonaviy usullari - Tangriberdiyev Xolmirzo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Within the evolution of the acoustic environment and digital audio workstations (DAW), the problem of psychoacoustic adaptation and technical errors in the sound engineer's receptive apparatus is intensifying. As part of the research object, the practical workflow of 34 specialists operating in the studios of the State Conservatory of Uzbekistan and local post-production facilities during 2021-2025 was empirically analyzed. Systemic deviations in spectral and dynamic balancing were found to have a direct correlation with the fatigue of the central nervous system's auditory receptors and improperly calibrated monitoring systems. Through A/B testing of audio materials and objective acoustic measurements, a syndrome of incorrect evaluation of low-frequency (20-250 Hz) signals was observed in 68% of the specialists. Empirical analyses dictate that phase shifts, over-compression, and the negative consequences of the masking effect significantly degrade the quality of the final product. This article proposes algorithmic models to bypass cognitive illusions and optimize acoustic control. The dynamics of the obtained results allow for increasing the clarity of the final phonogram by introducing ergonomic breaks and international calibration standards (ITU-R BS.1770) into sound recording practice.